Literasi Keuangan Syariah dalam Rumah Tangga: Model Pelatihan Manajemen Keuangan Islami untuk Keluarga Sejahtera di Desa Ulu Aer - Akhir Saleh Pulungan; Nur Lela Hasibuan; Mhd Irpan Nasution; Sinar Maito Nasution; Ali Akbar (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Islamic financial literacy plays a strategic role in creating household economic resilience, especially in rural areas. This study aims to formulate an Islamic financial management training model applicable for families in Ulu Aer Village. The research method employs a qualitative descriptive approach through literature review, observation, and focus group discussions with community leaders. The findings reveal that low financial literacy causes families to struggle in managing income and expenses. The proposed training model consists of five stages: financial problem identification, basic Islamic literacy training, practical workshops, application of Sharia principles, and mentoring and evaluation. Implementing this model is expected to enhance family financial management skills, reduce consumer debt burdens, and strengthen social solidarity through zakat, infaq, and sadaqah.